Clostridium perfringens type E virulence traits involved in gut colonization - Redondo, Leandro Martín; Diaz Carrasco, Juan María; Redondo, Enzo Alejandro; Delgado, Fernando Oscar; Fernandez Miyakawa, Mariano Enrique (PLOS, 2019)
Clostridium perfringens type E disease in ruminants has been characterized by hemorrhagic enteritis or sudden death. Although type E isolates are defined by the production of alpha and iota toxin, little is known about the pathogenesis of C. perfringens type E infections. Thus far, the role of iota toxin as a virulence factor is unknown. In this report, iota toxin showed positive effects on adherence and colonization of C. perfringens type E while having negative effect on the adherence of type A cells. In-vitro and in-vivo models suggest that toxinotype E would be particularly adapted to exploit the changes induced by iota toxin in the surface of epithelial cells. In addition, type E strains produce metabolites that affected the growth of potential intra-specific competitors. These results suggest that the alteration of the enterocyte morphology induced by iota toxin concomitantly with the specific increase of type E cell adhesion and the strong intra-specific growth inhibition of other strains could be competitive traits inherent to type E isolates that improve its fitness within the bovine gut environment.